The Impact of Public–Private Partnership on the Level of Medical Services Provided: An applied study of Saudi Arabian Airlines General Corporation and Fakeeh Medical Group - Nasrulddin, Vivian Mohammed; Almutaani, Amjad Matruh; Baobaid, Khulud Khalid; Alazwari, Ruba Abdullah; Alotaibi, Elaf Mohammed; Ayn Aldeen, Shahad Abdullah (Journal of Economic, Administrative and Legal Sciences, 2025)
The significance of this study lies in analyzing the impact of the strategic partnership in healthcare services between the Saudi Arabian Airlines Corporation, as a representative of the public sector, and Fakeeh Medical Group, as a representative of the private sector, in the Kingdom of Saudi Arabia during the period from January to June 2024. The research problem is framed by the following question: What is the impact of the partnership between the Saudi Arabian Airlines Corporation and Fakeeh Medical Group on the quality of healthcare services provided, through an analysis of appointment scheduling efficiency, waiting time, and the efficiency of medical examination services? The study adopted the descriptive-analytical approach, which focuses on accurately describing and analyzing phenomena. A questionnaire was employed as the primary data collection tool and was randomly distributed to a sample of 386 individuals. The collected data were analyzed using SPSS software, where multiple regression models were applied to test the research hypotheses and validate the relationships between the studied variables. The results indicate that the partnership between the public and private sectors plays an effective role in improving the quality and efficiency of healthcare services provided. Respondents expressed a high level of satisfaction with the quality of medical services. Furthermore, the study revealed a statistically significant relationship between the quality of healthcare services and each of the following factors: appointment scheduling efficiency, waiting time, and the efficiency of medical examination services. The regression coefficients for these variables were 0.289, 0.466, and 0.485, respectively, indicating that a one-unit increase in appointment scheduling efficiency, waiting time, and medical examination efficiency results in an increase in the quality of healthcare services by 28%, 46%, and 48%, respectively. In light of these findings.